2022
DOI: 10.1111/bcp.15227
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic characterization of favipiravir in patients with COVID‐19

Abstract: This prospective observational study describes the pharmacokinetic characteristics of favipiravir in adult patients hospitalized for mild to moderate COVID‐19 with a positive RT‐PCR test. Favipiravir was administered for 5 days, with a loading dose of 3200 mg and a maintenance dose of 1200 mg/day. Serial blood samples were collected on Day 2 and Day 4 of the therapy. Laboratory findings of the patients (n = 21) and in‐hospital mortality were recorded. Favipiravir concentrations exhibited substantial variabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Based on PK data, the FPV trough concentration substantially decreased by 89% between day 2 (21.26 μg/mL) and day 4 (1.6 μg/mL) after COVID-19 treatment in Turkish, with the majority having BMI > 25 kg/m 2 and predicted to decrease over time, while, the plasma concentration need > 20 μg/mL to achieve the 50% effective concentration (EC50) value (9.4 μg/mL). However, the trough concentration in healthy volunteers ranged from 20 to 60 μg/mL (Day 1: 600 mg bid, day 2–5: 600 mg bid) 26 28 . The population PK study showed that body surface area, dosage, and invasive mechanical ventilation were related to clearance and bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…Based on PK data, the FPV trough concentration substantially decreased by 89% between day 2 (21.26 μg/mL) and day 4 (1.6 μg/mL) after COVID-19 treatment in Turkish, with the majority having BMI > 25 kg/m 2 and predicted to decrease over time, while, the plasma concentration need > 20 μg/mL to achieve the 50% effective concentration (EC50) value (9.4 μg/mL). However, the trough concentration in healthy volunteers ranged from 20 to 60 μg/mL (Day 1: 600 mg bid, day 2–5: 600 mg bid) 26 28 . The population PK study showed that body surface area, dosage, and invasive mechanical ventilation were related to clearance and bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of favipiravir against several viral infections has emerged as possible therapy for COVID-19 [29]. The pharmacokinetic profile of favipiravir is quite complex [30]. Inconsistency in the efficacy outcomes of favipiravir treatment in many clinical studies can be attributed to a variety of factors, including research design, demographic, and ethnicity [31].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, FPV pharmacokinetics display high variability in COVID-19 patients, and higher doses may be necessary. 38 Similarly, for the NTZ component, we used a dose of 1000 mg BID with food, whereas recent pharmacokinetic modelling predicts an optimal dose of 1400 mg BID with food. 39 The FPV + NTZ arm had the highest frequency of adverse events in this study, though in healthy volunteers NTZ doses of up to 1500 mg are well tolerated.…”
Section: Discussionmentioning
confidence: 99%